Student’s Response in Online Learning Process: A Case Study of English Education Students - Rizqi Husaini (JETLe (Journal of English Language Teaching and Learning), 2020)
The purpose of this study was to look at the level of student activity in online lectures. This research method uses descriptive qualitative. In this research, the data source is all online lecture recording one of the colleges in Madiun contained in the online media platform used by the author. The research results found several exciting things that the level of activity of students in the discussion is excellent compared with offline lectures. Several things can affect, such as the level of student confidence, comfort in attending lectures, and enough time to read the material provided can be longer so that they can understand the material provided. So it can be concluded that online lectures are convenient for some things to apply in education.